Implementing and enforcing: UN arms embargoes lessons learned from various conflict contexts - Judith Vorrath (Stiftung Wissenschaft und Politik (SWP), 2020)
The Berlin Conference on Libya in January 2020 was held to support United Nations (UN) conflict-resolution efforts. The participating states' commitment to the existing arms embargo garnered particular attention. But hopes of meaningful progress were quickly dashed, with the embargo violated yet again shortly after the conference. Indeed, the implementation and enforcement of UN arms embargoes is fraught with challenges, especially prominently in the case of Libya. But closer examination of existing embargoes in the context of armed conflict also reveals opportunities for making better use of the measure, which is the most frequently used form of UN sanctions. It goes without saying that no arms embargo can save a peace process on its own, however tightly it is monitored. But the instrument can be applied to greater effect as part of an overall package of conflict resolution measures.
Keywords: 320